2009
DOI: 10.1126/science.1170905
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoenzymatic Cleavage of the Ultralarge Vascular Protein von Willebrand Factor

Abstract: Von Willebrand factor (VWF) is secreted as ultralarge multimers that are cleaved in the A2 domain by the metalloprotease ADAMTS13 to give smaller multimers. Cleaved VWF is activated by hydrodynamic forces found in arteriolar bleeding to promote hemostasis, whereas uncleaved VWF is activated at lower, physiologic shear stresses and causes thrombosis. Single-molecule experiments demonstrate that elongational forces in the range experienced by VWF in the vasculature unfold the A2 domain, and only the unfolded A2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

34
615
4
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 493 publications
(661 citation statements)
references
References 33 publications
34
615
4
3
Order By: Relevance
“…The results showed that only the unfolded A2 domain is cleaved by ADAMST-13. 62 These observations corroborated previous studies which found that shear-induced stretching of large vWF multimers results in the exposure of the scissile Tyr 1605 -Met 1606 bond within the A2 domain, facilitating cleavage by ADAMST-13 in normal plasma. 56,57 Smaller vWF multimers in microcirculation equally undergo stretching in regions of high shear, such as a bleeding arteriole, which expose bonding sites in the A1 domain of vWF for complexation with platelets during haemostasis.…”
Section: Effects Of Shear Flow On Protein Structure and Functionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results showed that only the unfolded A2 domain is cleaved by ADAMST-13. 62 These observations corroborated previous studies which found that shear-induced stretching of large vWF multimers results in the exposure of the scissile Tyr 1605 -Met 1606 bond within the A2 domain, facilitating cleavage by ADAMST-13 in normal plasma. 56,57 Smaller vWF multimers in microcirculation equally undergo stretching in regions of high shear, such as a bleeding arteriole, which expose bonding sites in the A1 domain of vWF for complexation with platelets during haemostasis.…”
Section: Effects Of Shear Flow On Protein Structure and Functionsupporting
confidence: 91%
“…62 Specifically, the study examined the folded and unfolded states of a single A2 domain of vWF, which contains the site of cleavage for ADAMST-13, in the presence and absence of the metalloprotease. The A2 domain of vWF was unfolded by directly applying force with laser tweezers.…”
Section: Effects Of Shear Flow On Protein Structure and Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The unfolding force, L c , and L p distributions are consistent with protein domain unfolding. This is supported by: (i) at 1000 nm/s pulling velocity, the unfolding force varies between 100-130 pN [13], (ii) the increase in the contour length for each added peak L c is 25 nm, consistent with the contour length of an unfolded full or partial VWF domain [13]; and (iii) the persistence length, L p , of 0.3 nm is consistent with an unfolded protein [13,20,[22][23][24][25][26]. Force-extension curves demonstrate that the VWF domains unfold in a sequential manner, producing one to four peaks for RDVWF [ Fig.…”
mentioning
confidence: 55%
“…3(d)]. These values correspond to the length of unfolded protein domains of 60 and 190 amino acids (aa), respectively, assuming 0.36 nm per residue [13,20,21]. The persistence length, L p , of the RDVWF was 0.3 nm [ Fig.…”
mentioning
confidence: 99%